Malignant Glaucoma: A Review of the Modern Literature. (27th March 2012) - Shahid, H.; Salmon, J. F.
Abstract : Malignant glaucoma is a rare form of glaucoma that typically follows surgery in patients with primary angle closure and primary angle-closure glaucoma. In this paper, the clinical features, classification, pathogenesis, and principles of management are discussed. Despite a high prevalence of primary angle closure glaucoma in South-East Asia, the vast majority of cases of malignant glaucoma are reported in White populations. This may reflect differing mechanisms of angle closure in White and Asian patients, which somehow reduces the likelihood of an aberrant relationship developing between the lens, ciliary body, anterior hyaloid, and vitreous structures within the eye. Although the exact underlying pathogenic mechanism remains unclear, the prognosis is good with modern medical, laser, and surgical treatment modalities.